Design of Cast Steel Components under Cyclic Loading - Nagel, Sven (Berichte zum Stahl- und Leichtbau, 2022)
This work presents a design approach that links fatigue resistance of cast steel component to permissible defect sizes. It is based on fractures mechanics, is in line with experiences of the last 60 years and validated by extensive experimental as well as numerical investigations on different scales and under consideration of real casting defects. By following established assessment methods, the design concept is adapted to practical building applications.